Improvement of memory guided saccades in parkinsonian patients by high frequency subthalamic nucleus stimulation. Issue 3 (1st March 2000) - Rivaud-Péchoux, Sophie; Vermersch, Anne-Isabelle; Gaymard, Bertrand; Ploner, Christoph J; Bejjani, Boulos P; Damier, Philippe; Demeret, Sophie; Agid, Yves; Pierrot-Deseilligny, Charles
Abstract : Recent studies in the monkey suggest that the subthalamic nucleus (STN) is involved in control of eye movement, yet its functional significance in humans is unknown. Saccadic eye movements were studied in eight parkinsonian patients treated by bilateral electrical stimulation of the STN. STN stimulation improved the accuracy of memory guided saccades but not of reflexive visually guided saccades and had no effect on the antisaccade task. This study shows that, by contrast with levodopa, STN stimulation improves memory guided saccade deficits, and illustrates for the first time in humans the role of the STN in the control of purposive saccades.